Behavior and Strength of Lightweight Sandwich Reinforced Concrete Beams - Vimonsatit, Vanissorn; Wahyuni, Ade; Nikraz, Hamid (Research Publishing Services, 2011)
A lightweight concrete section has been developed with a novel use of prefabricated autoclaved aerated concrete (AAC). This section, namely LSRC section, is a reinforced concrete section in which AAC bricks are used as infill material. An experimental investigation into the strength of LSRC beams has shown promising results under both flexural and shears tests. Based on the test results, the flexural capacity was found to be almost identical to the capacity of the equivalent solid beam, while the shear capacity was reduced. The shear strength reduction was as expected due to the reduction in the compressive strength of AAC infill material. This paper focuses on a numerical investigation into the behavior and strength of LSRC beams using ANSYS finite element method of analysis. A numerical model is developed and the analytical results are comparable with the experiment.